The use of language in the construal/ reflection of gender roles in media texts - Sandra DEGTIAR; Aistė ŠIAULYTĖ (Styles of Communication, 2023)
The perception of gender roles is a topic that has been growing over the past decade. The issue arises as society and culture, in general, and media, in particular, still impact the concepts of masculinity and femininity. The reason is that the function of a media article is not only to inform the reader but also to influence, conveying the ideology through a subjective prism. Distinct ideologies are expressed through language, consequently, the way language is used in media constructs distinct views on how women and men should behave in society. The aim of the article is to investigate linguistic features in online media texts in order to reveal how women and men are portrayed across British and American online media texts. The research is intended to explore distinct representations of gender roles found in media texts, regarding the language used, lexical and grammatical features, in particular, to reflect the images of men and women roles. Hence, the linguistic approach at the micro- and macro level resulted in the identification of 129 linguistic devices, of which modal meanings, emphatic adverbs, idioms were the most found in media texts. The use of distinct linguistic constructions enables writers to convey a wide range viewpoint, shaping or modifying the attitudes of their readers. Nevertheless, the study includes several linguistic levels (grammatical and lexical) and since there is a limited approach in the field, a deeper analysis could be conducted to gain a better understanding in this research area.